Analisis Program Cerdas Istimewa dalam Meningkatkan Penjaminan Mutu di MTsN 1 Kota Surabaya - Restu Agung Santoso; Amitasya Andriani; Sahudi Sahudi (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study discusses the implementation of the Cerdas Istimewa (CI) Program at MTsN 1 Surabaya City as an acceleration program aimed at improving educational quality assurance. The program was initiated to provide special educational services for students with above-average intelligence so that their potential could develop optimally. The CI Program is conducted over a two-year period through an intensive learning system with additional study hours and involves various parties, including selected teachers, counseling teachers, homeroom teachers, and full support from the madrasah administration. This article uses a qualitative research method with a case field reseach. The results of the study indicate that the acceleration program has made a significant contribution to improving school quality. This can be seen from the increasing reputation of the school at the national level, the high public interest in enrolling children in the CI Program, and the improvement in students’ motivation and academic achievement. In addition, the program has strengthened the image of MTsN 1 Surabaya City as a leading school capable of providing modern and competitive educational services. Nevertheless, the implementation of the acceleration program faces several challenges, such as student fatigue and stress caused by the intensive learning schedule. To address these issues, the school provides psychological assistance and additional time for completing assignments. Overall, the Cerdas Istimewa Program is considered effective in enhancing school quality assurance because it is able to produce high-achieving graduates, increase public trust, and strengthen the quality of educational services at MTsN 1 Surabaya City.